ANALYSIS OF THE EVIDENCE OF GEOTHERMAL POTENTIAL ZONE AND FAULT BY USING THE RESULTS OF MERCURY, RADON, AND THORON GASES MEASUREMENT IN WEST LEMBANG REGION, WEST JAVA - Mesaroziduhu Zebua Wanggai (NIM : 12114096), Hartman
Geothermal energy is one of many alternative renewable energy that can be categorized as sustainable and renewable energy. One of preliminary exploration method on the surface that is effective and low-cost can be done by measuring the concentration of mercury, radon, and thoron from soil gas in the surface area. Measuring the mercury, radon, and thoron gases is effective to discover the geothermal reservoir sources and the permeable zone due to fault. This research is accomplished by doing a measurement in 26 spots around the region of western part of Lembang from July to August 2018. The gas concentration is measured at the shallow-drilled hole with depth of 2 meters. The measurement is performed with three cycles a week. The measurement could done using EMP-2 Gold Analyzer. The concentration of mercury gas range between 1.25 ng/m3 – 77.63 ng/m3. The high anomaly concentration were found at KNCH and PDB at north western part of area. The high anomaly concentration value was spatially analyzed by correlating with some geological features i.e fault, lithology, and geothermal surface manifestation. It can be found the mercury concentration has positive correlation with the surface manifestation, but didn’t has spatial correlation with the concentration of radon, thoron, and radon/thoron gasses. The concentration of radon, thoron, and radon/thoron gases are effective to estimate the permeability zone due to fault. The mercury gas is not correlated with the lithology or the existence of the fault. The differences in mercury (gas) concentration at the same lithology is due to the evidence of a structure that extend north-south from Tangkuban Parahu, while the concentration of mercury gas is low at the Lembang fault zone. The result shows that Lembang fault is not connected to the geothermal system of Tangkuban Parahu. From the analysis, it can be indicated that there is a potential source of geothermal energy at the northwest of the research location at south of Tangkuban Parahu volcano.